Metaphysical Identification of Heidegger's Dasein - Seyed Masoud Zamani (حکمت و فلسفه, 2018)
According to the common sense, Dazein is the Heidegger's philosophical title on the general concept of man; i.e. man in the true sense. But a closer examination of Heidegger's works in the near future of existence and time shows that he in fact considers a particular type of human being. Thus, Heidegger attempts in various ways to clarify Determinations and existences of Dasein. One of his ways is to examine the distinction that Dasein takes from metaphysics. Dasein has a strong link with metaphysics, which Heidegger explores in detail in his works of those years. He even says that Dazean is the same as metaphysics. Thus, when Dasein is really Dasein that it is in front of metaphysics and its guidance question. On the other hand, Heidegger sees metaphysics as a completely specific and historical phenomenon that has only been realized in the West and not in any other nation or culture. But because the existence of the Dasein is definite to western metaphysics and its history, so Dasein can not be any human.The most important consequence of the current research is that Heidegger, with Dasein, in fact, considers a European man.